Saturday

April 19, 2014

April 19, 2014

Posted by **Jake** on Thursday, March 29, 2012 at 8:23pm.

I did this so far,

2k-1=5

6/2

k=3

- Calculus -
**Steve**, Friday, March 30, 2012 at 11:26amwhat's the problem?

(k,2k-1,3)•(k,5,-4) = k*k + (2k-1)(5) + 3(-4)

so, we need

k^2 + 10k - 5 - 12 = 7

k^2 + 10k - 24 = 0

(k-2)(k+12) = 0

so, k=2 or -12

k=2: (2,3,3)•(2,5,-4) = 4+15-12 = 7

k=-12: (-12,-25,3)•(-12,5,-4) = 144-125-12 = 7

**Related Questions**

Calculus - Dot Product - consider a rhombus ABCD a) find the resultant of vector...

Math - Product Dot Vectors - How would you expand and simplify the following ...

Mathematics - Dot Product - Consider rhombus ABCD a) Find the resultants of ...

calculus - Find two unit vectors that make an angle of 60° with v = ‹3, 4›. Give...

Calculus - Two force vectors act on an object and the dot product of the two ...

Vector Calculus - 2. Use the properties of the dot product to show that (⃗...

Math: Cross Product - Prove that | a x b | = (sqrt) [(a (dot) b)(b (dot) b) - (a...

Math - Vectors - If "u = (2,2,-1)", "v = (3,-1,0)" and "w = (1,7,8)", verify ...

CALCULUS - Rate of Change You are given the dollar value of a product in 2008 ...

Calculus - Calculate the dot product of two vectors: m = [4,5,-1] and n = [6,-2,...